1997
DOI: 10.1104/pp.113.4.1091
|View full text |Cite
|
Sign up to set email alerts
|

The glossy1 Locus of Maize and an Epidermis-Specific cDNA from Kleinia odora Define a Class of Receptor-Like Proteins Required for the Normal Accumulation of Cuticular Waxes

Abstract: Mutations at the glossyl (gll) locus of maize (Zea mays L.) quantitatively and qualitatively affect the deposition of cuticular waxes on the surface of seedling leaves. l h e gll locus has been molecularly cloned by transposon tagging with the Mutafor transposon system. l h e epi23 cDNA was isolated by subtractive hybridization as an epidermis-specific mRNA from Senerio odora (Kleinia odora). l h e deduced amino acid sequence of the GL1 and EP123 proteins are very similar to each other and to two other plant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 30 publications
0
74
0
Order By: Relevance
“…In contrast to cer1, the stems of wax2 are deficient in both aldehydes and alkanes (and its metabolites), suggesting that wax2's primary blockage ( Figure 10) occurs in the metabolic step preceding that blocked by cer1. Conversely, Hansen et al (1997) suggested that the homologous GL1 could not code for a decarbonylase because Phylogram derived from a data set of deduced polypeptides for Arabidopsis WAX2 and related deduced polypeptides. The rooted tree was constructed using CLUSTAL W (Thompson et al, 1994).…”
Section: The Wax2 Protein Functions In Cuticle Membrane and Wax Produmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to cer1, the stems of wax2 are deficient in both aldehydes and alkanes (and its metabolites), suggesting that wax2's primary blockage ( Figure 10) occurs in the metabolic step preceding that blocked by cer1. Conversely, Hansen et al (1997) suggested that the homologous GL1 could not code for a decarbonylase because Phylogram derived from a data set of deduced polypeptides for Arabidopsis WAX2 and related deduced polypeptides. The rooted tree was constructed using CLUSTAL W (Thompson et al, 1994).…”
Section: The Wax2 Protein Functions In Cuticle Membrane and Wax Produmentioning
confidence: 99%
“…the gl1 mutant actually had higher proportions of alkanes than the wild-type parent and the GL1 protein lacked the third Hisrich motif required for iron binding. Instead, based on the predicted secondary structure of GL1 and CER1, Hansen et al (1997) suggested that these proteins might belong to a superfamily of integral membrane receptors that are composed of a hydrophobic N-terminal domain with seven transmembrane-spanning regions and a globular water-soluble C-terminal domain (Probst et al, 1992). Although WAX2, CER1, and GL1 have comparable transmembrane structures, our analysis using Sequence BLAST and multiple alignments using CLUSTAL W 1.82 did not show high similarity to membrane receptors.…”
Section: The Wax2 Protein Functions In Cuticle Membrane and Wax Produmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the wax composition of the cer1 mutants (Hannoufa et al, 1993) and the histidine-rich motifs of the protein sequence (Aarts et al, 1995), CER1 has been proposed to encode an aldehyde decarbonylase. However, other possible functions for CER1 have been suggested (Hansen et al, 1997). The CER2 gene is likely to encode a biosynthetic enzyme, because it shares sequence similarity with acyl transferases (St-Pierre et al, 1998).…”
mentioning
confidence: 99%